Heart Disease Prediction Using Modified K-Means and Using Naive Baiyes - Mujawar, Sairabi; Devale, Prakash (International Journal of Computer Sciences and Engineering, 2025)
The health care industry is generally rich in information which is not feasible to handle manually. These large amounts of data are very important in the field of Data Mining to extract useful information and generate relationship amongst the attributes. In the health care industry, for predicting the diseases from the datasets data mining is used. Heart disease prediction is treated as most complicated task in the field of medical sciences. This paper investigates a number of techniques in the detection of heart disease. This paper includes a blueprint of application of data mining in heart disease prediction.